Modelling the behaviour of composite sandwich structures when subject to air-blast loading - Arora, H.; Hooper, P.; Del Linz, P.; Yang, H.; Chen, S.; Dear, J. (The international journal of multiphysics, 2012)
Large-scale glass fibre reinforced polymer (GFRP) and carbon fibre reinforced polymer (CFRP) sandwich structures (1.6 m x 1.3 m) were subject to explosive air blast (100 kg TNT equivalent) at stand-off distances of 14 m. Digital image correlation (DIC) was used to obtain full-field data for the rear-face of each deforming target. A steel plate of comparable mass per unit area was also subjected to the same blast conditions for comparison. The experimental data was then verified with finite element models generated in Abaqus/Explicit. Close agreement was obtained between the numerical and experimental results, confirming that the CFRP panels had a superior blast performance to the GFRP panels. Moreover all composite targets sustained localised failures (that were more severe in the GFRP targets) but retained their original shape post blast. The rear-skins remained intact for each composite target with core shear failure present.